How to think and act strategically: the pedagogical case study of haiti healthy kids - Santana, Joana Filipe (2015)
Nonprofit organizations are increasingly faced with the need to demonstrate their benefits, their value and to effectively operate in an ever competitive and dynamic environment. As a result, these organizations are required to focus on proper organizational strategies and to build strong strategic positions, as to become more efficient, attain long-term sustainability and, ultimately, drive organizational progress. Strategic thinking and acting are now major issues within the nonprofit sector and all organizations must strive to incorporate them. This pedagogical case study explores the strategic management process, a set of managerial decisions and tools that enable organizations to develop, implement and also control their organizational strategies and that facilitate superior performance, sustainability and further progress. It is focused on Haiti Healthy Kids, a small nonprofit health organization that delivers medical treatment to Haitian children and that lacks solid strategies and a strategic course of action that allows it to reach its fullest potential and desired results. Building on strategic management, the case develops the four stages of this process in light of Haiti Healthy Kids – it evaluates the environmental elements and internal features of the organization; it formulates viable strategies for it, considering strategic analysis; it suggests general guidelines for strategic implementation; and it identifies viable tools to control the impact of the strategies formulated. Ultimately, it reflects upon the overall benefits of this strategic approach for Haiti Healthy Kids. The selection and application of the strategic management principles and instruments aim to properly address and solve this organizational problem, and also to enhance the readers’ learning and expertise in this subject. At the same time, this case study is a valuable and an useful working instrument that highlights the importance of strategy, strategic planning and management for nonprofits’ effectiveness and sustainability.